Strategi Pengembangan Ekonomi Lokal Berkelanjutan Pada Kawasan Minapolitan - Meisyaroh Catur Wulandari; jaka nugraha (Universitas Negeri Surabaya, 2021)
Region area has economic potential, including Gondosuli Village, which has been determined to have the potential for a minapolitan area. The process of exploiting the potential of the local economy requires a partnership formed by the local government and the community. Local economic development through regional development must have a well-targeted development strategy. The purpose of this research is to describe the local economic development strategy and the supporting and inhibiting factors in the Minapolitan area. The research method used is a qualitative method and used a descriptive approach. The analytical method used Miles and Huberman method because this method is considered to be able to answer the researcher's objectives. The results of the research show that Gondosuli Village as a minapolitan center area in Tulungagung Regency has become an independent fishery area and as a pilot area for aquaculture.